Effect of self-care education via distance learning and the reversal method on self-care behaviors and quality of life in patients with heart failure: A quasi-experimental study - Zahra Khezerlou; Nader Aghakhani; Rozita Cheraghi; Vahid Alinejad (Journal of Nursing Advances in Clinical Sciences)
This study aimed to determine and compare the impact of self-care education using distance learning and the reversal method on self-care behaviors and the quality of life in patients with heart failure. This quasi-experimental study was conducted with 90 patients with heart failure who visited the Seyed al-Shohada Educational and Medical Center in Urmia between 2021 and 2022. The patients were randomly assigned to three groups: the reversal education group, the distance learning group, and the control group. The control group received routine educational care, while the reversal method group was evaluated through in-person questioning to assess their understanding, where patients were asked to explain what they had learned in their own words. The distance learning group received instruction via WhatsApp. Data were analyzed using paired t-tests, analysis of variance (ANOVA), analysis of covariance (ANCOVA), and chi-square tests in the Statistical Package for the Social Sciences (SPSS) version 22. The results showed that the mean self-care and quality of life scores among the three groups (control, reversal, and distance learning) before the intervention were not statistically significant (P>0.05). However, after the intervention, the mean scores of self-care education and quality of life, except for the physical dimension, were statistically significant among the three groups (P=0.0001). Based on the positive impact of both the reversal and distance learning methods on self-care and quality of life in heart failure patients, it is recommended to use these two educational methods due to their simplicity and ease of application in educating these patients.